A Noneist Account of the Doctrine of Creatio ex Nihilo - Kabay, Paul Douglas (Sophia, 2013)
I spell out a problem with the doctrine of creatio ex nihilo: that, contra the doctrine, it is not possible to efficiently cause something from nothing. This is because an efficient cause requires a material cause in order to have an effect. The material cause supplies the potency that the efficient cause actualises. Because nothingness has no potencies, there is nothing for an efficient cause to actualise. I show that this objection presupposes that the theory of noneism (the proposition that some things do not exist) is false. I postulate that the universe (i.e. the created order) is a non-existent item and so there is no problem with the claim that it was efficiently caused to come from nothing – the universe has no being anyway. After rehearsing the rather strong reasons in favour of the truth of noneism, I deal with two objections that are peculiar to my claim that the universe lacks reality: that creation possesses characteristics that are sufficient to render it existent and that a non-existent object has its properties independent of divine fiat. I show that there are sensible replies to both objections. With regard to the first I show that the possession of such characteristics at most shows that the universe has an ontological status that is equivalent to some reference point. With regard to the second I argue that the Characterisation Principle (i.e. in some world – not necessarily the actual world – an object has the properties that it is characterised as having) entails that non-existent objects possess their properties in virtue of some existent entity and that the only plausible candidate for such an entity is a divine mind of some sort.